Northern Borneo stalagmite records reveal West Pacific hydroclimate across MIS 5 and 6 - Carolin, Stacy A.; Cobb, Kim M.; Jean, Lynch-Stieglitz; Moerman, Jessica W.; Partin, Judson W.; Lejau, Syria; Malang, Jenny; Clark, Brian; Andrew A., Tuen; Adkins, Jess F. (Elsevier, 2016)
Over the past decades, tropical stalagmite δ18Orecords have provided valuable insight on glacial and interglacial hydrological variability and its relationship to a variety of natural climate forcings. The transition out of the penultimate glaciation (MIS 6) represents an important target for tropical hydroclimate reconstructions, yet relatively few such reconstructions resolve this transition. Particularly, comparisons between Termination1 and 2 provide critical insight on the extent and influence of proposed climate mechanisms determined from paleorecords and model experiments spanning the recent deglaciation. Here we present a new compilation of western tropical Pacific hydrology spanning 0–160kyBP, constructed from eleven different U/Th-dated stalagmite δ18Orecords from Gunung Mulu National Park in northern Borneo. The reconstruction exhibits significant precessional power in phase with boreal fall insolation strength over the 0–160kyBP period, identifying precessional insolation forcing as the dominant driver of hydroclimate variability in northern Borneo on orbital timescales. A comparison with a network of paleoclimate records from the circum-Pacific suggests the insolation sensitivity may arise from changes in the Walker circulation system. Distinct millennial-scale increases in stalagmite δ18O, indicative of reduced regional convection, occur within glacial terminations and may reflect a response to shifts in inter-hemispheric temperature gradients. Our results imply that hydroclimate in this region is sensitive to external forcing, with a response dominated by large-scale temperature gradients.